System and Procedures for Opening an IB Maslahah Deposit Account at Bank BJB Syariah KCP Indramayu - Laelatur Rizan (Konsultan Jurnal Ilmiah Indonesia, 2025)
iB Maslahah Deposit Savings is one of the products of BJBS KCP Indramayu Bank. The existence of this product is an implementation of sharia banking services that provide investment alternatives in accordance with sharia principles. The iB Maslahah Deposit product at BJB Syariah bank uses the Mudharabah Mutlaqah contract, namely the contract used in deposit products in sharia banking, where the customer (shahibul maal) deposits funds to the bank (mudharib) to be managed freely by the bank in accordance with sharia principles. In a mudharabah mutlaqah agreement, the bank has complete freedom in managing customer funds without any restrictions or special instructions regarding how and where to manage these funds, as long as it adheres to provisions in accordance with Islamic law. The research method used is descriptive qualitative with a case study approach at Bank BJB Syariah KCP Indramayu. Data was obtained through interviews with banks and direct observation of the deposit account opening process. The Ib Maslahah Deposit System at Bank BJB Syariah KCP Indramayu has profit sharing given in accordance with the ratio determined at the time of the contract. The purpose of this research is to determine the system and procedures for opening a deposit account with a Mudharabah Mutlaqah agreement at PT. Bank Jabar Banten Syariah Indramayu Sub-Branch Office. The research results show the system and process for opening an Ib Maslahah Deposit account at PT. Bank Jabar Banten Syariah Indramayu Sub-Branch Office.